A Ternary Eutectic Solvent for Cellulose Nanocrystal Production: Exploring the Recyclability and Pre-Pilot Scale-Up - Ruiz-Leon, D; Ruiz-Leon, D (Frontiers Media SA, 2023)
Deep eutectic solvents (DES) formed using choline chloride (ChCl), p-toluenesulfonic acid (pTSA) of stoichiometry ChCl: pTSA (1:1) and (1:2), and its ternary eutectic mixtures with phosphoric acid (PA) 85% as an additive (ChCl: pTSA: PA) were evaluated for cellulose nanocrystal (CNC) isolation. Initially, the hydrolytic efficiency to produce CNC of each DES was compared before and after adding phosphoric acid by Hammett acidity parameters and the Gutmann acceptor number. Moreover, different DES molar ratios and reaction time were studied at 80°C for CNC optimization. The nanomaterial characteristics were analyzed by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA). The ternary eutectic mixture ChCl: pTSA: PA molar ratio (1:1:1.35) was chosen as a suitable recyclable ternary system at the laboratory scale. A CNC yield of about 80% was obtained from the hydrolysis of commercial cellulose in five cycles of recovery, but it dropped to 35% in pre-pilot scaling. However, no variation in the average size of the resulting CNC was observed (132 ± 50 nm x 23 ± 4 nm), which presented high thermal stability (Tmax 362°C) and high crystallinity of about 80% after 3 h of reaction time. Copyright © 2023 Mariño, Paredes, Martinez, Millan, Tapia, Ruiz, Isaacs and Pavez.